Pengaruh Persepsi Bank Syariah di Indonesia terhadap Customer Switching Intention dengan Customer Satisfaction sebagai Mediator - Anisa Miftahul Jannah; Arry Widodo (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
Indonesia's banking industry is still dominated by conventional banking. Sharia banking in Indonesia should use competitive marketing strategies and pay particular attention to the behavior of communities to compete in the national and global banking environment. This study aims to determine the effect of perception of sharia banks in Indonesia to customer switching intention with mediated by customer satisfaction. This research uses descriptive analysis method. Data collection techniques using questionnaires with Likert scale distributed to 100 customers of conventional banks. Hypothesis testing is done by using PLS (Partial Least Square). The results of this study indicate that the perception of sharia banks affect positively and significantly to customer satisfaction and influence directly or indirectly through customer satisfaction as a mediator of customer switching intention. Keywords: Perception, Customer Satisfaction, and Customer Switching Intention.